870 Investigating sexual dimorphism in the tumor immune microenvironment of non-muscle invasive bladder cancer. (9th November 2020) - Chenard, Stephen; Jackson, Chelsea; Vidotto, Thiago; Hardy, Celine; Jamaspishvilli, Tamara; Berman, David; Siemens, David Robert; Koti, Madhuri
Abstract : Background: While the incidence of non-muscle invasive bladder cancer (NMIBC) is four times higher in men than women, female patients display earlier recurrence than their male counterparts following treatment with Bacillus Calmette-Guerin (BCG) immunotherapy. 1 While patient sex (biological differences) and gender (social/behavioral differences) have long been associated with NMIBC incidence and clinical outcome, these factors remain the most understudied phenotypes in biomarker and treatment design. 2 We hypothesized that sexual dimorphism in the pre-existing tumor immune microenvironment (TIME) may contribute to the poor clinical outcomes observed in female NMIBC patients. Methods: To test this hypothesis, we interrogated the expression patterns of genes associated with specific immune cell populations and immune checkpoint pathways using tumor transcriptome profiles from n=460 NMIBC patients (357 males and 103 females). Based on this interrogation, we utilized multiplex immunofluorescence to selectively evaluate the density and spatial distribution of CD79a+ (B), CD163+ (M2-like tumor associated macrophages), and PD-L1+ (programmed death ligand 1) cells in an independent cohort of 510 NMIBC tumors collected from n=390 patients (305 males and 85 females). Results: We observed significantly higher expression of immune checkpoints genes CTLA4, PDCD1, TIGIT, LAG3 and ICOS in tumors from female patients. Importantly, transcript levels of the B cell recruiting chemokine CXCL13 and the B cell surface molecule CD40 were significantly increased in tumors from female patients. Multiplex immunofluorescence revealed that CD163+ cells were significantly higher in epithelial and stromal compartments of high-grade tumors (p = 0.0011, p = 0.00034, respectively) from female patients compared to males. While no sex-associated differences were observed in the density of CD79a+ B cells, this population was found to be significantly increased in the epithelial and stromal compartments (p = 6.9e-9, 9.4e-10, respectively) of high-grade tumors compared to low-grade tumors. PD-L1 expression was significantly higher in the epithelial compartment of high-grade tumors from female patients (p = 0.04). Kaplan-Meier survival analysis showed that higher density of CD163+ and CD79a+ cells were independently associated with shorter recurrence free survival (RFS). Notably, these differences in RFS remained in BCG immunotherapy-naïve patients (n=170). Conclusions: These findings are the first evidence of sexual dimorphism in the TIME of NMIBC and may help to partially explain the worse clinical outcomes experienced by female patients. This study also provides the first evidence of the negative prognostic impact of B cells in NMIBC. Overall, this study provides insight into more rational implementation of immune-based therapies in female NMIBC patients. Ethics Approval: This study was approved by the Ethics Review Board at Queen's University, Kingston, ON, Canada. References: Saginala K, Barsouk A, Aluru JS, Rawla P, Padala SA, Barsouk A. Epidemiology of bladder cancer. Med Sci 2020;8. Uhlig A, Strauss A, Seif Amir Hosseini A, Lotz J, Trojan L, Schmid M, et al . Gender-specific differences in recurrence of non-muscle-invasive bladder cancer: a systematic review and meta-analysis. Eur Urol Focus 2018;4:924–36.